Economics of gynecologic morcellation. Issue 1 (February 2018) - Bortoletto, Pietro; Friedman, Jaclyn; Milad, Magdy P.
Abstract : Purpose of review: As the Food and Drug Administration raised concern over the power morcellator in 2014, the field has seen significant change, with patients and physicians questioning which procedure is safest and most cost-effective. The economic impact of these decisions is poorly understood. Recent findings: Multiple new technologies have been developed to allow surgeons to continue to afford patients the many benefits of minimally invasive surgery while minimizing the risks of power morcellation. At the same time, researchers have focused on the true benefits of the power morcellator from a safety and cost perspective, and consistently found that with careful patient selection, by preventing laparotomies, it can be a cost-effective tool. Summary: Changes since 2014 have resulted in new techniques and technologies to allow these minimally invasive procedures to continue to be offered in a safe manner. With this rapid change, physicians are altering their practice and patients are attempting to educate themselves to decide what is best for them. This evolution has allowed us to refocus on the cost implications of new developments, allowing stakeholders the opportunity to maximize patient safety and surgical outcomes while minimizing cost.